Authoritarian Parenting Style of the Main Character in the Novel a Child Called “It” by Dave Pelzer - Safitri, Nada Fira; Pertala, Erik Candra; Hestiana, Siska (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2024)
The research entitled "The Main Character's Authoritarian Parenting Style in the Novel A Child Called 'It' by Dave Pelzer" is focused on identifying and describing the authoritarian parenting style of the main character in Dave Pelzer's novel. In addition, this study also identifies and describes the impact of authoritarian parenting by the main character on children in the novel. This study uses a qualitative descriptive method, with an objective approach to describe and illustrate authoritarian parenting and the impact of authoritarian parenting by the main character on children who are included in the intrinsic elements of the novel. Data collection which was carried out uses note-and-read techniques, in which the reading of the novel A Child Called 'It' involved all dialogues in the novel to determine the actions of the main character's authoritarian parenting and the impact of authoritarian parenting on children contained in the novel. The results of this study indicate that authoritarian parenting is a form of parenting that is not good for children. This is indicated by the presence of some unfavorable parental behavior towards children. This study shows that the authoritarian parenting style is divided into four parts and each part shows how the behavior of parents with authoritarian parenting style towards children. The impact of authoritarian parenting is divided into two parts, namely the positive impact and the negative impact. Authoritarian parenting can have a positive impact even though more negative impacts are received by children. Keywords: The main character, Authoritarian parenting style, A Child Called “It” novel